2005
DOI: 10.1038/sj.cdd.4401668
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial complex I activity is impaired during HIV-1-induced T-cell apoptosis

Abstract: Studies carried out till date to elucidate the pathways involved in HIV-1-induced T-cell depletion has revealed that apoptosis underlie the etiology, however, a clear molecular understanding of HIV-1-induced apoptosis has remained elusive. Although evidences pointing towards the importance of mitochondrial energy generating system in apoptosis exist but it's exact role remains to be clearly understood. Here, we describe for the first time specific downregulation of a complex I subunit NDUFA6 with simultaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 50 publications
5
63
0
2
Order By: Relevance
“…These proteins are the homologues of N. crassa NUO78 (29) and NUO30.4 (60), respectively. Specific downregulation of NDUFA6 (homologue of N. crassa NUO14.8 [41]) but not other complex I subunits induces apoptosis in cells infected with HIV-1 (33). With the possible exception of NDUFA6, the other human complex I subunits were described as proapoptotic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins are the homologues of N. crassa NUO78 (29) and NUO30.4 (60), respectively. Specific downregulation of NDUFA6 (homologue of N. crassa NUO14.8 [41]) but not other complex I subunits induces apoptosis in cells infected with HIV-1 (33). With the possible exception of NDUFA6, the other human complex I subunits were described as proapoptotic.…”
Section: Discussionmentioning
confidence: 99%
“…2). Complex I has been implicated in cell death induced by human viruses (33,53) or other stimuli in both human and fungal cells (8,31,34,39). Specific subunits of mammalian complex I have also per se been implicated in cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Other work has shown that complex I inhibition induces apoptosis in mammalian cells (45,46) and that caspase cleavage of the 75-kDa subunit of complex I was claimed to be required for apoptosis (47). Furthermore, it appears that complex I is also involved in virus-induced apoptosis (48,49) and in the interferon-ā¤ and retinoic acid-induced cancer cell death (50). Our results are in line with these findings and point to a central role of complex I in mediating programmed cell death in filamentous fungi.…”
Section: Discussionmentioning
confidence: 99%
“…The perturbations in the metabolite profile were related to increased production of NADH (NADH/NAD + ratio) and FADH 2 due to the dysfunctional RC. Impaired functioning of components of the RC has also been reported as a consequence of HIV infection (Ricci et al 2004;Ladha et al 2005). …”
Section: Metabolic Interpretations Of the Markers Of Hiv Infectionmentioning
confidence: 99%